Pharmacoeconomic analysis of the application of strong opioids for the treatment of chronic pain syndrome in patients with pancreatic cancer - O. P. Bobrova; S. K. Zyryanov; N. A. Shnayder; M. M. Petrova (IRBIS LLC, 2021)
Objective: to evaluate the clinical and economic feasibility of opioid therapy based on the analysis of its cost and effectiveness in patients with chronic pain syndrome in pancreatic cancer.Material and methods. An observational prospective study in parallel groups of patients with chronic pain syndrome associated with pancreatic cancer was carried out. The analysis of cost minimization and cost-effectiveness was applied, as well as pharmacoeconomic modeling, which included the construction of a decision tree in patients receiving morphine sulfate (n=45) and fentanyl TTS (n=45) for pain relief. The sensitivity of the obtained data was assessed using one-way analysis.Results. It was shown that the treatment of chronic pain syndrome in patients with pancreatic cancer with opioid analgesics as part of combined treatment is the least expensive in the morphine sulfate group (incremental cost-effectiveness ratio 144.93). Based on the results of modeling, the prognostic factors of influence on the cost of analgesic therapy were determined: the cost of combined analgesic therapy, the cost of treatment of adverse reactions, and the cost-effectiveness ratio.Conclusion. Analgesic therapy of chronic pain syndrome with morphine sulfate in patients with pancreatic cancer is pharmacoeconomically feasible.